2014
DOI: 10.1002/glia.22627
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated repair of demyelinated CNS lesions in the absence of non‐muscle myosin IIB

Abstract: The oligodendrocyte (OL), the myelinating cell of the central nervous system, undergoes dramatic changes in the organization of its cytoskeleton as it differentiates from a precursor (OPC) to a myelin-forming cell. These changes include an increase in its branching cell processes, a phenomenon necessary for OL to myelinate multiple axon segments. We have previously shown that levels and activity of non-muscle myosin II (NMII), a regulator of cytoskeletal contractility, decrease as a function of differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Adult mice (8 w) were used for the lysolecithin‐induced demyelination model (Figure a,b). We measured maximal lesion volume 7 days post‐injection (dpi), the peak time of demyelination in the lysolecithin model (Rusielewicz et al, ), and found that demyelination volume (fluoromyelin‐negative area) did not significantly change in the corpus callosum between Cx43 cKO and WT mice (Figure c,d). Given that lysolecithin is toxic to myelinating cells and causes rapid OL death as well as demyelination after injection (Gregson & Hall, ), our results showed that Cx43 deletion in astrocytes had no influence on OL response to lysolecithin in the corpus callosum.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Adult mice (8 w) were used for the lysolecithin‐induced demyelination model (Figure a,b). We measured maximal lesion volume 7 days post‐injection (dpi), the peak time of demyelination in the lysolecithin model (Rusielewicz et al, ), and found that demyelination volume (fluoromyelin‐negative area) did not significantly change in the corpus callosum between Cx43 cKO and WT mice (Figure c,d). Given that lysolecithin is toxic to myelinating cells and causes rapid OL death as well as demyelination after injection (Gregson & Hall, ), our results showed that Cx43 deletion in astrocytes had no influence on OL response to lysolecithin in the corpus callosum.…”
Section: Resultsmentioning
confidence: 97%
“…To further investigate the impact of astrocytic Cx43 on the remyelination process, we compared myelin integrity between Cx43 cKO and WT mice at 14 dpi (Figure a), which is the typical remyelination stage. We identified the lesion area by DAPI labeling, and observed aggregated nuclei as previously described (Figure b) (Mei et al, ; Rusielewicz et al, ). MBP staining showed that the nonremyelinated area in the corpus callosum was smaller in Cx43 cKO mice than in WT mice, indicating that remyelination progress was accelerated upon the absence of Cx43 in astrocytes (Figure b,c).…”
Section: Resultsmentioning
confidence: 99%
“…The group of Melendez‐Vasquez has contributed significantly to the knowledge of non‐muscle myosin IIB in OL biology. Non‐muscle myosin IIB is involved in OL contractility and was found to be a negative regulator of differentiation and myelination (Rusielewicz et al, ; Wang et al, ; Wang, Tewari, Einheber, Salzer, & Melendez‐Vasquez, ). The expression of non‐muscle myosin IIB decreases during in vitro maturation of primary rat OLs (Figure b) (Wang et al, ).…”
Section: Oligodendrocyte Mechanosensing For Myelinationmentioning
confidence: 99%
“…In terms of localization, non‐muscle myosin IIB is highly expressed in OPCs, where it co‐localizes with actin filaments at the tips of growing protrusions and is also present in OPC protrusion branches and the cortex (Wang et al, ). In a model of lysolecithin‐induced demyelination and remyelination, it was shown that depletion of non‐muscle myosin IIB enhanced myelin repair by promoting OL maturation (Rusielewicz et al, ). Altogether, these data support a role for myosin IIB in OPC branching and differentiation.…”
Section: Oligodendrocyte Mechanosensing For Myelinationmentioning
confidence: 99%
“…Increased morphological complexity is preceded by inactivation of RhoA and consequent decrease of actomyosin contractility, since RhoA activates ROCK (Rho kinase)—the inducer of NMM-II (Figure 2B). Concomitantly, inhibition or abrogation of myosin-II accelerates OL differentiation—leading to increased expression of MBP and cellular branching (Wang et al, 2008, 2012)—and potentiates remyelination after lysolecithin-induced demyelination in adult mice (Rusielewicz et al, 2014). …”
Section: Mechanical Modulation Of Oligodendrocytesmentioning
confidence: 99%